Holographic photon production in heavy ion collisions - Ioannis Iatrakis (Journal of High Energy Physics, 2017)
Abstract The thermal-photon emission from strongly coupled gauge theories at finite temperature is calculated using holographic models for QCD in the Veneziano limit (V-QCD). The emission rates are then embedded in hydrodynamic simulations combined with prompt photons from hard scattering and the thermal photons from hadron gas to analyze the spectra and anisotropic flow of direct photons at RHIC and LHC. The results from different sources responsible for the thermal photons in QGP including the weakly coupled QGP (wQGP) from perturbative calculations, strongly coupled N $$ \mathcal{N} $$ = 4 super Yang-Mills (SYM) plasma (as a benchmark for reference), and Gubser’s phenomenological holographic model are then compared. It is found that the direct-photon spectra are enhanced in the strongly coupled scenario compared with the ones in the wQGP, especially at high momenta. Moreover, both the elliptic flow and triangular flow of direct photons are amplified at high momenta for V-QCD and the SYM plasma. The results are further compared with experimental observations.